ANALISIS SWOT DALAM STRATEGI PENGEMBANGAN BISNIS USAHA MINYAK GORENG CURAH PADA CV PROSPECT MANDIRI SEJAHTERA LAMONGAN - Zuleo Erico; M. Suyanto; Yulyar Kartika Wijayanti (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
Developing a bulk cooking oil business strategy at CV Prospect Mandiri Sejahtera Lamongan using SWOT and BMC analysis as a reference to determine strengths, weaknesses, opportunities and threats. As well as knowing in detail about strategic management tools to define and communicate business ideas or concepts quickly and easily. The aim of this final assignment is to find out the factors that influence the competitiveness of CV Prospect Mandiri Sejahtera and to find out business development strategies that can be implemented by CV Prospect Mandiri Sejahtera in expanding the market share and competitiveness of bulk cooking oil in Lamongan. Based on the analysis of the table of internal factors and external factors, it shows that the strength factor (S) has a score of 2.33 and weakness (W) with a score of 0.97. Meanwhile, the opportunity factor (O) has a score of 2.25 and the threat factor (T) has a score of 1.13. So you can get an IFAS score of 3.30 and an EFAS score of 3.39. The total score of internal strategic factor analysis (IFAS) obtained a score of 3.30, this shows that CV Prospect Mandiri Sejahtera has great strength to face opportunities and threats that occur. The total score of external strategic factor analysis (EFAS) which has been weighted and rated is 3.39 shows that CV Prospect Mandiri Sejahtera is quite responsive to the opportunities and threats that occur.